(untitled) (American Journal of Islam and Society, 1986)
I. Introduction A. The Science of Anthropology This study is speculative and concerns a difficult and complex subject. Its task is made more difficult as it defends a metaphysical position, advances an ideological argument, and serves a moral cause. It will therefore remain an incomplete part of an on-going process in the debate on key issues in contemporary Muslim society. The major task of anthropology’ -the study of man-is to enable us to understand ourselves through understanding other cultures. Anthropology makes us aware of the essential oneness of man and therefore allows us to appreciate each other. It is only quite recently in history that it has come to be widely accepted that human beings are fundamentally alike; that they share basic interests, and so have certain common obligations to one another. This belief is either explicit or implicit in most of the great world religions, but it is by no means acceptable today to many people even in "advanced" societies, and it would make no sense at all in many of the less-developed cultures. Among some of the indigenous tribes of Australia, a stranger who cannot prove that he is a kinsman, far from being welcomed hospitably, is regarded as a dangerous outsider and may be speared without compunction. Members of the Lugbara tribe of northwestern Uganda used to think that all foreigners were witches, dangerous, and scarcely human creatures who walked about upside-down and killed people by magic. The ancient Greeks believed that all non-Hellenic peoples were barbarians and uncivilized savages whom it would be quite inappropriate to treat as real people. Many citizens of modem states today think of people of other races, nations, or cultures in ways not very different from these, especially if their skin is differently colored or if ...